Quotatives : new trends and sociolinguistic implications - Buchstaller, Isabelle (Language in society (Oxford, England), 2014)
"Quotatives considers the phenomenon "quotation" from a wealth of perspectives. It consolidates findings from different strands of research, combining formal and functional approaches for the definition of reported discourse and situating the phenomenon in a broader typological and sociolinguistic perspective. Provides an interface between sociolinguistic research and other linguistic disciplines, in particular discourse analysis, typology, construction grammar but also more formal approaches Incorporates innovative methodology that draws on discourse analytic, typological and sociolinguistic approaches Investigates the system both in its diachronic development as well as via cross-variety comparisons Presents careful definition of the envelope of variation and considers alternative definitions of the phenomenon "quotation" Empirical findings are reported from distribution and perception data, which allows comparing and contrasting perception and reality "--